Penyederhanaan Birokrasi pada Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat - Masitoh, Siti; Kushendar, Deden Hadi; Mulawarman, Aditia (Universitas Batanghari Jambi, 2024)
Simplification in the bureaucracy is one of the focuses of the 5 (five) priority programs of the Onward Indonesia Cabinet under the leadership of President Joko Widodo and Ma'ruf Amin and as a presidential mandate which is an executive order that must be carried out. We must continue to simplify the bureaucracy on a large scale. Investment for job creation must be prioritized. This study aims to determine the simplification of bureaucracy in the Regional Library and Archives Office of West Java Province. The method used in this study is qualitative by using data collection techniques by observing, interviewing and documenting. The results of this study are that the services available at the Regional Library and Archives Service of West Java Province are appropriate and in the alignment of administrative positions to functional positions because the simplification of the bureaucracy has the advantage that services become simpler, agile, fast and less verbose Regional Library and Archives Services West Java Province simplified the bureaucracy on the basis of government policy with the aim of facilitating the delivery of services to the community more quickly.